Effect of Peripheral Layer on Peristaltic Transport of a Micropolar Fluid - Prasad, K. M. M.; Radhakrishnamacharya, G. (Nonlinear Analysis: Modelling and Control, 2009)
Peristaltic transport of two fluid model with micropolar fluid in the core region and Newtonian fluid in the peripheral layer is studied under the assumptions of long wavelength and low Reynolds number. The linearised equations governing the flow are solved and closed form expressions for pressure rise, time averaged flux and frictional force have been obtained. The effects of various parameters on these flow variables have been studied. It is found that the pressure rise increases with micropolar parameter (m) and central mean radius (η), but decreases with coupling number (N) and viscosity ratio (µ¯). The frictional force (F¯) decreases with coupling number (N) and viscosity ratio (µ¯) but increases with micropolar parameter (m) and mean radius of central layer (η).